Faktor-Faktor Yang Mempengaruhi Praktik Manajemen Laba (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to examine the effect of managerial ownership,institutional ownership, information asymmetric, leverage, and profitability on the earningsmanagement in manufacturing companies listed in Indonesia Stock Exchange in the period2017-2019. This research used 38 samples which are selected using purposive samplingtechnique. This research used secondary data such as financial statement and annual reportof manufacturing companies listed in Indonesia Stock Exchange during 2017-2019. Thisresearch used EViews 11.0 to process the data. The result of this research shown thatinformation asymmetric and leverage have positive significant effect on earningsmanagement, while managerial ownership, institutional ownership, and profitability have nosignificant effect on earnings management.